Guided Bone Regeneration to Improve Osseointegration in Dental Implant - Yuliati Yuliati; Agnes Paramitha Nastiti; Pratiwi Soesilawati; Muhammad Alwino Bayu Firdauzy; Aspalilah Alias; Nazmul Haque (Malaysian Journal of Medicine and Health Sciences, 2024)
Indexed by Scopus/MyCite